Translation features of terminological vocabulary (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the importance of scientific and technical translation owing to the rapid development of technology and scientific and technical information distribution. It shows the importance of the development of skills through the study of vocabulary and grammatical structures characteristic to this type of literature. The importance of the creative mental abilities of a translator which are the basis for this profession is emphasized.
Keywords: term; translation; scientific and technical text; glossary of terms